Modelling of water supply cost for offshore platforms - Nuraihan, Ismail; Mohd Zamani, Ahmad; Mohd Nasir, Hussain; Amalina Nisa, Ariffin; Ismail, Zainol (IJSTR, 2019)
An offshore platform like other industries requires water resources to support daily operation and activities. Supplying water to offshore platform mainly executed in two conventional ways: transported using offshore supply vessel and self- produced onboard platform using seawater desalination process commonly known as a freshwater generator. An alternative method such as water reuse or water recycling also received growing attention as one of a promising integrated solution for improvement of water resources. However, each water supply options have different characteristics and limitations in term of supply capacity, cost associated and level of water quality. Hence, it’s difficult to identify which water supply sources that fulfil the demand and cost-effective. This paper proposes a new mathematical model namely Economic Water Supply Model (EWSM) for the operating cost function that includes the most representative variables in the process. This model enables decision-makers and owners to assess the economic value from the different sources of water supply for the offshore platform. The calculation of these extended cost function also enables a detailed comparison to be made of the various water sources from an economic of view in order to analyze the effects of supply capacity for costeffective of various suppliers. In this sense, a model of the structure costs associated with each of the available water supply technologies can be useful input for future design, planning and operational stage of offshore water supply process.